A single-cell atlas of the peripheral immune response to severe COVID-19 - Wilk, Aaron J; Rustagi, Arjun; Zhao, Nancy Q; Roque, Jonasel; Martinez-Colon, Giovanny J; McKechnie, Julia L; Ivison, Geoffrey T; Ranganath, Thanmayi; Vergara, Rosemary; Hollis, Taylor; Simpson, Laura J; Grant, Philip; et al. (medRxiv : the preprint server for health sciences, 2020)
There is an urgent need to better understand the pathophysiology of Coronavirus disease 2019 (COVID-19), the global pandemic caused by SARS-CoV-2. Here, we apply single-cell RNA sequencing (scRNA-seq) to peripheral blood mononuclear cells (PBMCs) of 7 patients hospitalized with confirmed COVID-19 and 6 healthy controls. We identify substantial reconfiguration of peripheral immune cell phenotype in COVID-19, including a heterogeneous interferon-stimulated gene (ISG) signature, HLA class II downregulation, and a novel B cell-derived granulocyte population appearing in patients with acute respiratory failure requiring mechanical ventilation. Importantly, peripheral monocytes and lymphocytes do not express substantial amounts of pro-inflammatory cytokines, suggesting that circulating leukocytes do not significantly contribute to the potential COVID-19 cytokine storm. Collectively, we provide the most thorough cell atlas to date of the peripheral immune response to severe COVID-19.